Deltoid Analysis of Pakistan-ASEAN-China Free Trade Agreements and Opportunities for Pakistan - Irshad, Muhammad Saqib; Xin, Qi; Xuan, Li; Arshad, Hamza (Asian Economic and Financial Review, 2016)
The interaction of nations shaped by their bilateral ties and the multilateral associations in the shape of triangles demonstrates an opportunity to acknowledge some interesting and motivating dynamics of the existing international trade relations among nations. This study on Pakistan- Association of Southeast Asian Nations-China Free Trade Agreement is an effort to highlight the potentials of the structure of this triangle and opportunities for Pakistan. The analysis shows Pakistan trade with China and ASEAN countries is rapidly growing in recent years but exports are still in lacking position. China-Pakistan Economics Corridor totally favorable for Pakistan and it will create more opportunities and long terms benefits for Pakistan. FTA with ASEAN is really potential from which Pakistan can get advantage in various areas to make cooperation such as trade and industry, environment, investment, science and technology, narcotics control, information technology, agriculture, education, tourism and human resource development. Pakistan and ASEAN countries share familiar aspirations for peace, development and prosperity of the region: therefore, it will be great if both parties can cooperate on a larger scale to benefit from each other.